2018
DOI: 10.17235/reed.2018.5674/2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long course and short course preoperative radiotherapy in the treatment of locally advanced rectal cancer: a systematic review and meta-analysis

Abstract: Background: rectal cancer (RC) is one of the most prevalent malignancies worldwide and different preoperative radiotherapies may lead to different outcomes. This meta-analysis aimed to compare the effectiveness of long-course (LC) and shortcourse radiotherapy (SC), with or without chemotherapy, for locally advanced rectal cancer. Methods: studies published up to March 31 st 2018 were retrieved from PubMed, Medline, Cochrane and EMABSE. Randomized control or consort control trials that reported the outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Similarly to other meta-analyses, PLCCRT increased the rate of grade 3-4 acute toxicity (RR = 0.13, P < 0.00001) and pCR (RR = 0.15, P = 0.003). Similar outcomes have been found in a recent systematic review and meta-analysis performed by the Chinese group of Yu et al [ 92 ]. Sixteen studies with a total of 2.773 rectal cancer patients were included in the pooled analysis.…”
Section: Resultssupporting
confidence: 90%
“…Similarly to other meta-analyses, PLCCRT increased the rate of grade 3-4 acute toxicity (RR = 0.13, P < 0.00001) and pCR (RR = 0.15, P = 0.003). Similar outcomes have been found in a recent systematic review and meta-analysis performed by the Chinese group of Yu et al [ 92 ]. Sixteen studies with a total of 2.773 rectal cancer patients were included in the pooled analysis.…”
Section: Resultssupporting
confidence: 90%
“…Second, our patients received consolidation chemotherapy during the interval of chemoradiotherapy and TME, which had been confirmed efficient in improving the pCR rate in previous studies [13,17]. Third, comparing to the former group which used short-course radiotherapy with 3 cycles of FOLFOX4, our R0 resection rate was slightly higher, probably because the concurrent chemotherapy may enhance the efficacy of preoperative treatment [18], even though no direct evidence was found to demonstrate the superiority of conventionally fractionated radiation to short-course radiation [16,19]. Finally, the addition of oxaliplatin to fluorouracil-based chemotherapy has been reported to be more efficient in preoperative treatment [8,9].…”
Section: Discussionsupporting
confidence: 54%
“…This may be because the SC group received more preoperative chemotherapy. A previous meta-analysis found that LC presented a better pCR rate compared with the SC without chemotherapy, meaning that chemotherapy may enhance the efficacy of preoperative treatment [ 12 ]. Another randomized phase III study by Bujko et al [ 13 ] compared patients receiving radiotherapy (5 × 5 Gy) and three cycles of FOLFOX4 with those receiving 50.4 Gy in 28 fractions combined with two 5-day cycles of bolus 5-Fu 325 mg/ m 2 /day and leucovorin 20 mg/m 2 /day during the first and fifth week of irradiation along with five infusions of oxaliplatin 50 mg/m 2 once weekly.…”
Section: Discussionmentioning
confidence: 99%